การรับรู้ของนักศึกษาต่อการปฏิบัติงานของอาจารย์ผู้สอนนักศึกษา ระดับปริญญาโท บัณฑิตวิทยาลัย วิทยาลัยทองสุข - หิรัญนิธิธำรง, ดร.ฐิติพัฒน์ (วารสาร ศึกษาศาสตร์ มมร; Vol 3 No 2 (2015): วารสารศึกษาศาสตร์ มมร ปีที่ 3 ฉบับที่ 2 (กรกฎาคม-ธันวาคม 2558), 2015)
การวิจัยครั้งนี้มีวัตถุประสงค์ เพื่อศึกษา 1) ระดับการรับรู้ของนักศึกษาต่อการปฏิบัติงานของอาจารย์ผู้สอนนักศึกษาระดับปริญญาโท บัณฑิตวิทยาลัย วิทยาลัยทองสุข 2) เปรียบเทียบการรับรู้ของนักศึกษาต่อการปฏิบัติงานของอาจารย์ผู้สอนนักศึกษาระดับปริญญาโท บัณฑิตวิทยาลัย วิทยาลัยทองสุข กลุ่มตัวอย่างได้แก่ นักศึกษาระดับปริญญาโท จำนวน 123 คน ได้มาจากการสุ่มแบบช่วงชั้น เครื่องมือที่ใช้ในการวิจัยเป็นแบบสอบถามที่ผู้วิจัยพัฒาขึ้น มีค่าความเชื่อมั่นทั้งฉบับเท่ากับ .98 สถิติที่ใช้ในการวิเคราะห์ข้อมูลได้แก่ ความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน การทดสอบสมมติฐานและการวิเคราะห์ความแปรปรวนทางเดียว วันเวย์อโนว่า ผลการวิจัยพบว่า 1) การรับรู้ของนักศึกษาต่อการปฏิบัติงานของอาจารย์ผู้สอนนักศึกษาระดับปริญญาโท บัณฑิตวิทยาลัย วิทยาลัยทองสุข โดยภาพรวมอยู่ในระดับมาก เมื่อพิจารณาเป็นรายด้านส่วนใหญ่คือ การรับรู้ทักษะการสอนของผู้สอน รองลงมาคือการรับรู้คุณภาพการสอนของผู้สอน และน้อยที่สุดคือ การรับรู้ความพึงพอใจในการปฏิบัติงานของผู้สอน ตามลำดับ 2) เปรียบเทียบการรับรู้ของนักศึกษาต่อการปฏิบัติงานของอาจารย์ผู้สอนนักศึกษาระดับปริญญาโท บัณฑิตวิทยาลัย วิทยาลัยทองสุข จำแนกตามสาขาวิชาต่างกันมีการรับรู้ของนักศึกษาต่อการปฏิบัติงานของอาจารย์ผู้สอนนักศึกษาระดับปริญญาโทโดยภาพรวมไม่แตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 Abstract  These research proposals were to 1) investigate the performance perception of Students to Master Degree Courses’ lecturers, Graduated School, Thongsook College level, and 2) compare the performance perception of Students to Master Degree Courses’ lecturers, Graduated School, Thongsook College. The 123 master degree students were be the samples which randomized by stratified random sampling. The research toolkit was the questionnaire which developed by the researcher self that got .98 reliability alpha coefficient statistical significantly. Finally, the data statistics analytical were frequency, percentage, mean, standard deviation, hypothesis test, and one way ANOVA (One Way Analysis Of Varience). The research found that; 1) the performance perception of Students to Master Degree Courses’ lecturers, Graduated School, Thongsook College level got high total level, when considered to each aspect found that the first one was the inspectors’ instruction skills perception, the secondly was the inspectors’ instruction qualities perception, and the last one was the inspectors’ instruction performance satisfactions perception, as sequent. 2) the comparison of the performance perception of Students to Master Degree Courses’ lecturers, Graduated School, Thongsook College, which classified to difference major learning programs got no difference performance perception of Students to Master Degree Courses’ lecturers, Graduated School, Thongsook College, as .05 statistical significance totally.